Interconnectedness of Factors Affecting Patient Willingness to Discuss Prostate Cancer Clinical Trials With Physicians - Janaka S.S. Liyanage; Vy Ong; Lauren M. Hamel; Susan Eggly; Michael A. Carducci; Dina G. Lansey; Elisabeth I. Heath; Tanina F. Moore; Terrance L. Albrecht; Mark A. Manning; Seongho Kim (JCO Oncology Practice, 2026)
PURPOSE Racial disparities in prostate cancer clinical trial participation persist. Sociodemographic and psychosocial predictors of willingness to discuss trials are often studied in separate models that do not account for intercorrelations. Using consent-time data from the Partnering Around Cancer Clinical Trials (PACCT) study (ClinicalTrials.gov identifier: NCT02906241 ), we examined multidimensional group-based medical mistrust (GBMM) and related factors within one structural equation model (SEM). METHODS We conducted a cross-sectional secondary analysis of patient-reported data at consent from 286 Black and White men with prostate cancer enrolled in PACCT phases I and II (November 2016-February 2021) at two National Cancer Institute-designated centers. Willingness and general trust in physicians were observed variables; GBMM was a latent construct (suspicion, disparities, lack of support subscales). Models used robust maximum likelihood in lavaan (239 of 286 with complete SEM data). RESULTS Higher GBMM (β = −.247; P = .028) and older age (β = −.217; P = .004) were associated with lower willingness; higher education (β = .176; P = .019) was associated with higher willingness. Black ( v White) race was associated with higher GBMM (β = .555; P < .001) and had a significant indirect association with willingness through GBMM (β = −.137; P = .035), not a significant direct path. Higher income was associated with greater GBMM (β = .221; P = .020) and lower physician trust (β = −.268; P = .002) but not with willingness. CONCLUSION Willingness to discuss trials reflected an interconnected pattern in which multidimensional GBMM was central. Findings are exploratory and associational and support patient-centered trial communication where mistrust may be salient, tailored discussions for older patients, and accessible information where comprehension needs may apply. Longitudinal evaluation of PACCT interventions is needed.